The Cadre Development Model of Wahdah Islamiyah Preachers: An Analysis of the Integration of Formal and Non-Formal Education - Samsuddin, Samsuddin; Iskandar, Iskandar; Agusman, Agusman; Masuwd, Mowafg; Abdurrahman, Abdurrahman (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2025)
The development of Islamic da’wah in the digital era presents new challenges for Islamic organizations in producing preachers (da’i) who are not only knowledgeable but also adaptive to social, technological, and cultural transformations. The fragmentation between formal and non-formal education in many da’wah institutions has weakened the continuity between the spiritual, intellectual, and social aspects of preacher formation. In this context, Wahdah Islamiyah becomes a significant case to study, as it has successfully developed a cadre system that integrates education, training, and da’wah in a holistic and systematic manner. This study aims to analyze the da’wah and preacher training system of Wahdah Islamiyah as a comprehensive model of institutional da’wah. The research employs a library-based qualitative approach with critical analysis of primary and secondary sources, including relevant previous studies. The results indicate that Wahdah Islamiyah successfully integrates da’wah bil lisan (preaching by speech), bil hal (by action), and bil qalam (by writing) within a multi-level and structured cadre system oriented toward character formation. This model emphasizes three main educational dimensions—ruhiyah (spiritual), tsaqafiyah (intellectual), and jasadiyah (physical)—which are crystallized into five core cadre characteristics: mu’min, mushlih, mujahid, muta’awin, and mutqin. The study highlights a key novelty: Wahdah Islamiyah perceives da’wah not merely as a spiritual activity but as an educational, social, and cultural strategy that aligns with the needs and challenges of the digital age. The findings contribute conceptually and practically to the development of da’wah organization strategies, the strengthening of Islamic education, and the formulation of contextual and inclusive religious policies. [Perkembangan dakwah Islam di era digital menghadirkan tantangan baru bagi organisasi Islam dalam melahirkan kader da’i yang tidak hanya berwawasan keilmuan, tetapi juga adaptif terhadap perubahan sosial, teknologi, dan budaya global. Fragmentasi antara pendidikan formal dan non-formal di berbagai lembaga dakwah menyebabkan lemahnya kesinambungan antara aspek spiritual, intelektual, dan sosial kader da’i. Dalam konteks tersebut, Wahdah Islamiyah menarik untuk dikaji karena berhasil mengembangkan sistem kaderisasi yang memadukan pendidikan, pembinaan, dan dakwah secara integral. Penelitian ini bertujuan menganalisis sistem dakwah dan kaderisasi da’i Wahdah Islamiyah sebagai model dakwah institusional yang komprehensif. Metode penelitian yang digunakan adalah studi kepustakaan dengan analisis kritis terhadap literatur primer dan sekunder, termasuk temuan penelitian terdahulu yang relevan. Hasil penelitian menunjukkan bahwa Wahdah Islamiyah berhasil mengintegrasikan dakwah bil lisan, bil hal, dan bil qalam dalam sistem kaderisasi da’i yang berjenjang, sistematis, dan berorientasi pada pembentukan karakter. Model kaderisasi ini menekankan tiga dimensi utama pendidikan, yaitu ruhiyah, tsaqafiyah, dan jasadiyah, yang kemudian dikristalisasi dalam lima karakter inti kader: mu’min, mushlih, mujahid, muta’awin, dan mutqin. Temuan penelitian ini menegaskan kebaruan bahwa Wahdah Islamiyah tidak hanya memandang dakwah sebagai aktivitas spiritual, tetapi juga sebagai strategi pendidikan, sosial, dan kultural yang relevan dengan kebutuhan serta tantangan era digital. Implikasi penelitian ini memberikan kontribusi konseptual dan praktis bagi pengembangan strategi organisasi dakwah, penguatan pendidikan Islam, dan perumusan kebijakan keagamaan yang kontekstual serta inklusif.]